2010
DOI: 10.1002/ijc.25710
|View full text |Cite
|
Sign up to set email alerts
|

Arg72Pro TP53 polymorphism and cancer susceptibility: A comprehensive meta‐analysis of 302 case‐control studies

Abstract: Arg72Pro is a common polymorphism in TP53, showing differences in its biological functions. Case-control studies have been performed to elucidate the role of Arg72Pro in cancer, although the results are conflicting and heterogeneous. Here, we analyzed pooled data from case-control studies to determine the role of Arg72Pro in different cancer sites. We performed a systematic review and meta-analysis of 302 case-control studies that analyzed Arg72Pro in cancer susceptibility. Odds ratios were estimated for diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
77
2
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 49 publications
2
77
2
2
Order By: Relevance
“…9 Several studies have highlighted the risk-modifying effect of these polymorphisms in common cancers and the rare Li-Fraumeni syndrome caused by germinal TP53 mutations. [10][11][12] The possible role of the MDM2 309SNP in RB has only recently been addressed through a family-based approach. 13 For the first time we here investigated both SNPs.…”
mentioning
confidence: 99%
“…9 Several studies have highlighted the risk-modifying effect of these polymorphisms in common cancers and the rare Li-Fraumeni syndrome caused by germinal TP53 mutations. [10][11][12] The possible role of the MDM2 309SNP in RB has only recently been addressed through a family-based approach. 13 For the first time we here investigated both SNPs.…”
mentioning
confidence: 99%
“…Similarly, the most recent meta-analysis indicated that the codon 72 polymorphism may not be associated with breast cancer risk in a Caucasian population. However, previous meta-analyses concerning the p53 codon 72 polymorphism also revealed conflicting results (23)(24)(25)(26). The precise reasons for this discrepancy remained to be elucidated (8,11).…”
Section: Discussionmentioning
confidence: 98%
“…One possibility is that the effect of this polymorphism varies according to the genetic background of the studied population. Francisco et al suggested that ethnicity and histological and anatomical sites modulate the penetrance of R72P in cancer susceptibility (26). The other possibility includes the size of the studied population and stringent levels of statistical significance (7).…”
Section: Discussionmentioning
confidence: 99%
“…A high heterogeneity of results was observed in breast Hu et al, 2010b;Lu et al, 2011b;Ma et al, 2011;Peng et al, 2011;Sergentanis and Economopoulos, 2010b;The Breast Cancer Association Consortium, 2006;Zhang et al, 2010b;Zhuo et al, 2009a), colon and rectum (Dahabreh et al, 2010;Liu et al, 2011;Tang et al, 2010;Wang et al, 2010b) cancers. Though still not quite clear, cancer of the ovary (Schildkraut et al, 2009;Zhang et al, 2008), endometrium (Francisco et al, 2010;Jiang et al, 2010b), stomach (Francisco et al, 2010;Gao et al, 2009;Liu et al, 2011), bladder (Jiang et al, 2010a;Li et al, 2010), prostate Zhang et al, 2011b;Zhu et al, 2011), and skin (Francisco et al, 2010;Jiang et al, 2011) appear to be affected. As for the rs17878362 polymorphism, a clear association of the A2 allele with a high risk of breast cancer Hu et al, 2010a;Hu et al, 2010b;Zhang et al, 2011a) and a lack of involvement in lung (Hu et al, 2010a), ovary (Schildkraut et al, 2009), colon and rectum (Hu et al, 2010a) cancer susceptibility has been demonstrated.…”
Section: Tp53 Polymorphisms: the Cancer Predisposing Valuementioning
confidence: 99%
“…However, in spite of the present disagreements and methodological flaws, association tendencies for some cancer localizations are clear (Table 2). Simply stated, the rs1042522 C allele is associated with increased susceptibility to cancers, including of the lung (Dai et al, 2009;Francisco et al, 2010;Li et al, 2009;Yan et al, 2009), head and neck (Francisco et al, 2010), thyroid (Francisco et al, 2010), esophagus Zhao et al, 2010), pancreas , liver Francisco et al, 2010), gallbladder , nasopharynx (Zhuo et al, 2009b), and cervix (Francisco et al, 2010;Klug et al, 2009). No significant contribution of TP53 rs1042522 polymorphism to oral cancer has been reported (Zhuo et al, 2009c).…”
Section: Tp53 Polymorphisms: the Cancer Predisposing Valuementioning
confidence: 99%